PENYUSUNAN DAN KUALITAS INDIKATOR KINERJA PADA SISTEM PENGUKURAN KINERJA ORGANISASI PERANGKAT DAERAH - Ayu Umyana (Journal of Islamic Economy and Business (JIsEB), 2021)
Abstract One of the problems that occur in the application of organizational performance measurement systems is due to inconsistencies in performance indicators that can lead to an illogical relationship between the performance indicators used. This has the potential for bias in the performance measurement process. This study aims to identify factors that influence the preparation and quality of an indicator of performance measurement. This study is also aimed at identifying trends in regional organizations to respond the practice of performance measurement based on mechanisms in institutional isomorphism. This study uses a mixed method through a survey process and direct interviews with respondents with research samples of state officials and civil servants (ASN) in the Sleman District Government. The results of this study indicate that factors about the organizational goals and objectives become a significant factor in the formulation of performance indicators. Meanwhile, problems related to limited performance data, knowledge and ability to interpret are not a significant factor in the formulation of indicators. The results also show that the validity of measurements, internal support and usefulness are aspects that need to be prioritized in assessing the quality of a measurement indicator. Based on the results of the study it was found that the tendency of government organizations in responding to performance measurement practices is based on the need and encouragement of professionalism. This characteristic indicates the occurrence of normative isomorphism in the application of performance measurement practices in Sleman Regency. Keywords: Institutional institutional theory, institutional isomorphism, performance indicators, performance measurement systems.